Aromaterapi Lavender sebagai Penurun Tingkat Kecemasan Persalinan - Annisa Ridha Salsabilla (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Anxiety is mental condition filled with worry about what might happen. Anxiety will increase when the mother feels the pain of giving birth to her baby. Strategy to reduce anxiety level can use lavender aromatherapy by doing massage or inhalation. Purpose: To determine the benefits of lavender aromatherapy as a reduction in labor anxiety levels. Method: The method used by the author is literature study from various national and international journals. This method is used with the aim of presenting, increasing knowledge and understanding of the topics discussed by summarizing the material that has been published and providing factual information or new analysis from relevant literature reviews and then comparing the results in the article. Results: lavender containing camphor, terpinen-4-ol, linalool, linalyl acetate, beta-ocimene and 1, 8-cineole was proven effective as a Complementary and Alternative Medicine analgesic that can reduce the level of labor anxiety, either applied by inhalation or massage. Conclusion: Lavender aromatherapy can be used to reduce the level of anxiety of labor.